2019
DOI: 10.1016/j.molimm.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Porcine deltacoronavirus nsp15 antagonizes interferon-β production independently of its endoribonuclease activity

Abstract: Porcine deltacoronavirus (PDCoV) is an emerging swine coronavirus causing diarrhea and intestinal damage in nursing piglets. Previous work showed that PDCoV infection inhibits type I interferon (IFN) production. To further identify and characterize the PDCoV-encoded IFN antagonists will broaden our understanding of its pathogenesis. Nonstructural protein 15 (nsp15) encodes an endoribonuclease that is highly conserved among vertebrate nidoviruses (coronaviruses and arteriviruses) and plays a critical role in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…More recently, it was proposed that NendoU activity of Nsp15 is responsible for the protein interference with the innate immune response, 11 though other studies indicate that the process is independent of the endonuclease activity. 12 There are also suggestions that Nsp15 degrades viral RNA to hide it from the host defenses. Nevertheless, Nsp15 is essential in coronavirus biology.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was proposed that NendoU activity of Nsp15 is responsible for the protein interference with the innate immune response, 11 though other studies indicate that the process is independent of the endonuclease activity. 12 There are also suggestions that Nsp15 degrades viral RNA to hide it from the host defenses. Nevertheless, Nsp15 is essential in coronavirus biology.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was proposed that NendoU activity of Nsp15 is responsible for the protein interference with the innate immune response (Deng et al, 2017) though other studies indicate that the process is independent of the endonuclease activity (Liu et al, 2019). While initially Nsp15 was thought to directly participate in viral replication, it was later shown that Nsp15-deficient coronaviruses were viable and replicating, rising doubts about the enzyme role in that process.…”
Section: Introductionmentioning
confidence: 99%
“…One of these proteins, NSP15 a nidoviral RNA uridylate-specific endoribonuclease (NendoU) containing carboxy-terminal catalytic domain linked to the EndoU family (Deng & Baker, 2018). Previous study has suggested that Nsp15 has crucial role in evasion of host defense mechanism and loss of EndoU function results in protective immune response (Deng & Baker, 2018;Liu et al, 2019). Therefore, Nsp15 is considered critical in coronavirus biology.…”
Section: Introductionmentioning
confidence: 99%